Implementing SaaS-Based Sales Force Automation Systems - Roy, Subroto; Bandyopadhyay, Nirmalya (Indian Journal of Marketing, 2022)
Business-to-business sales force automation (SFA) is changing rapidly, with complex products and services that frequently require team selling and a long sales cycle. With SaaS (Software as a Service), cloud-based systems, data entry, and analytics can be performed from a low-cost back office or by accessible, affordable technology. As a result, salespeople no longer need to work as “lone wolves.” Instead, they can become part of “partnering” sales teams as the physical front end of a multichannel, value-creating customer relationship management force. This paper offered a theory-based analytical framework for enhancing SaaS-based digitization in the form of a relational selling and behavioral control matrix.